Cellulose nanofibers derived from elephant grass incorporating anthocyanin extract from red dragon fruit peel as a natural fish freshness sensor - ’Aisy, Deuriya Rahadatul; Febiyanti, Rahma Aulia; Virshanda, Aurelia Ghefira Alifia (EcoVision: Journal of Environmental Solutions, 2026)
Background: This study presents the development of cellulose nanofibers (CNF) derived from elephant grass incorporated with anthocyanin extract from red dragon fruit peel as a natural fish-freshness sensor. The research is motivated by the increasing demand for eco-friendly, rapid, and practical freshness-detection technologies to address food-safety challenges associated with fish spoilage. Methods: A literature-based Research and Development (R&D) framework was employed to formulate extraction procedures, cellulose purification steps, and CNF–anthocyanin film fabrication. Anthocyanin was extracted using an ethanol–citric acid solvent system, while CNF was produced through deep eutectic solvent (DES) pretreatment, bleaching, and ultrasonic disintegration. Findings: The resulting CNF anthocyanin films demonstrated pH-sensitive color transitions associated with volatile nitrogenous compounds released during fish spoilage, indicating their potential application as visual freshness sensors. Conclusion: The study concludes that integrating CNF with natural anthocyanins provides a stable, renewable, and environmentally friendly approach suitable for smart packaging applications. Novelty/Originality of this article: The novelty of this work lies in the utilization of elephant-grass-derived CNF combined with red dragon fruit peel anthocyanins to create an innovative natural sensor material for monitoring fish freshness.